2018
DOI: 10.1177/0954408918780524
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the transient characteristics and volute casing wall pressure fluctuations of a single-blade pump

Abstract: In contrast to conventional multiblade centrifugal pumps, single-blade pumps are characterized by a significant fluctuation of head and highly transient and circumferentially nonuniform flow field even in the best-efficiency point. For a contribution to a better understanding of the flow field and an improvement of numerical methods, a combined experimental and numerical study is performed with special emphasis on the analysis of the transient pressure field. In an open test rig, piezoresistive pressure sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…While numerous studies have investigated the pressure fluctuation and unsteady characteristics in different kinds of pumps, which includes the effects of working conditions [14,16], inlet guide vanes [17], tip clearance [18], and volute curvature [19][20][21], but the influence of the number of diffuser vanes on the pressure fluctuation in the centrifugal pump is unclear and further investigation is needed. So, in this paper a numerical approach was adopted in a centrifugal pump with a different number of diffuser vanes, and the pressure fluctuations are analyzed and compared in detail.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have investigated the pressure fluctuation and unsteady characteristics in different kinds of pumps, which includes the effects of working conditions [14,16], inlet guide vanes [17], tip clearance [18], and volute curvature [19][20][21], but the influence of the number of diffuser vanes on the pressure fluctuation in the centrifugal pump is unclear and further investigation is needed. So, in this paper a numerical approach was adopted in a centrifugal pump with a different number of diffuser vanes, and the pressure fluctuations are analyzed and compared in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The residuals for continuity and momentum drop at least five orders of magnitude, while variations in global mass flow imbalance and averaged bulk output quantities between successive revolutions are below 1%. A similar approach was adopted by Melzer et al, 26 suggesting that these considerations offer adequate confidence in the numerical solution. The CFD software used for the numerical simulations was ANSYS FLUENT 19.2.…”
Section: Mesh and Numerical Setupmentioning
confidence: 97%
“…For this reason, the error bars around the experimental data are larger than would be expected from a well-controlled laboratory experiment. 26 The values from the numerical simulations are averaged over the final revolution. Figure 5(a) shows the head-discharge curve.…”
Section: Effect Of the Gap On Pump Performancementioning
confidence: 99%
“…16(b)), the measured head curve is only qualitatively captured, since the experimental data is numerically under-predicted. This underestimation is at first glance unexpected since several authors experienced an over-prediction of pump head in the simulation of centrifugal pumps, e.g., Barrio et al (2010), Limbach and Skoda (2017), and Melzer et al (2019), which is assumed to be attributed to the neglect of roughness effects in the simulation or the simulation's limitation of resolving secondary flows, e.g., flow separation. However, in other studies also an underestimation of experimental data is observed, which is assumed to occur mainly due to limitations of both the numerical grid and the turbulence model, e.g., Zhang et al (2018) and Perissinotto et al (2019).…”
Section: Grid Studymentioning
confidence: 99%